Chronic nausea and vomiting: insights into underlying mechanisms. Issue 5 (May 2016) - Törnblom, H.; Abrahamsson, H.
Abstract: Chronic nausea and vomiting are common and debilitating symptoms in adults. There are some fundamental problems that make our understanding of mechanisms difficult, diagnostic definitions of patient‐cohorts being central. As there is no unifying mechanism with a direct link to chronic nausea or vomiting, it is most likely that several mechanisms interact, e.g., pylorus function and its relation to gastric emptying, or gastric sensory and motor function. In this mini‐review, we highlight the roles and evidence for brain–gut interactions as well as gastrointestinal neurophysiologic, motor, sensory, and hormonal factors involved in the pathophysiology of chronic nausea and vomiting. There are factors not mentioned in the text, mostly as they are not well characterized in the setting of chronic symptoms or only in animal models. Abstract : Chronic nausea and vomiting of unknown cause are common and debilitating symptoms in adults. It is most likely that several pathophysiologic mechanisms interact. This mini‐review highlight the evidence for some key factors involved.